Fenomena dalam Keberlangsungan Usaha Tempe di Desa Tersono Kabupaten Batang - Alfina Ika Febriyanti; Eka Aniqotul Khasanah; Rauly Sijabat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The tempeh-making business is a small business that is crucial to the rural economy. However, this business faces various challenges, both economic and environmental. This study aims to understand how the tempeh business can continue to operate in Tersono Village, Batang Regency. This study examines the challenges faced, the strategies used, and the factors influencing the business's continued operation. The research method used was qualitative with a phenomenological approach. Data were collected through interviews with business owners, direct field observations, and document collection. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that the main challenges facing the tempeh business in Tersono Village are fluctuating soybean prices, which increase production costs, competition between businesses, limited labor availability, and the impact of water quality and weather on the fermentation process. To survive, businesses maintain product quality by selecting quality ingredients and adapting production methods to weather conditions. The factors most influencing the sustainability of the tempeh business are soybean prices, the skills and experience of the business owners, customer satisfaction, and environmental conditions. The sustainability of the tempeh business in Tersono Village is a socio-economic phenomenon that demonstrates the ability of small and medium enterprises (MSMEs) to adapt and survive in the face of business and environmental dynamics.